Perancangan Sistem Informasi Persediaan Stok Dan Pemesanan Beras Dengan Menggunakan Bahasa Pemrograman Php Dan Database Mysql (Studi Kasus : Huller Armaini) - Handayani, Putri; Deni Rizky, Syafrika; Syahputra, Hadi (Riset Sinergi Indonesia (RISINDO), 2024)
The main problem encountered in stock supplies and ordering rice is that there are many factors in various types of rice that can influence the quality of the rice itself. There needs to be an assessment to determine the quality of rice. This can be done using a model that can determine the quality of rice in accordance with the criteria desired by consumers. to get the best quality rice. This will have a good impact on the company if the quality of the rice matches consumer demand, as a result the company will experience an increase in production because the type of rice meets the criteria desired by consumers. And the rice company exports its rice to rice shops and restaurants. In designing a stock inventory and rice ordering information system using PHP and MySQL, we can integrate these two technologies to build a web application that is effective and efficient in managing stock inventory and carry out the rice ordering process. With this system, it is hoped that it can help rice business owners manage stock inventories, carry out ordering processes more quickly and easily, and increase business efficiency and productivity.